Global prevalence of sarcopenia and severe sarcopenia: a systematic review and meta‐analysis. Issue 1 (23rd November 2021) - Petermann‐Rocha, Fanny; Balntzi, Viktoria; Gray, Stuart R.; Lara, Jose; Ho, Frederick K.; Pell, Jill P.; Celis‐Morales, Carlos
Abstract: Background: Sarcopenia is defined as the loss of muscle mass and strength. Despite the seriousness of this disease, a single diagnostic criterion has not yet been established. Few studies have reported the prevalence of sarcopenia globally, and there is a high level of heterogeneity between studies, stemmed from the diagnostic criteria of sarcopenia and the target population. The aims of this systematic review and meta‐analysis were (i) to identify and summarize the diagnostic criteria used to define sarcopenia and severe sarcopenia and (ii) to estimate the global and region‐specific prevalence of sarcopenia and severe sarcopenia by sociodemographic factors. Methods: Embase, MEDLINE, and Web of Science Core Collections were searched using relevant MeSH terms. The inclusion criteria were cross‐sectional or cohort studies in individuals aged ≥18 years, published in English, and with muscle mass measured using dual‐energy x‐ray absorptiometry, bioelectrical impedance, or computed tomography (CT) scan. For the meta‐analysis, studies were stratified by diagnostic criteria (classifications), cut‐off points, and instruments to assess muscle mass. If at least three studies reported the same classification, cut‐off points, and instrument to measure muscle mass, they were considered suitable for meta‐analysis. Following this approach, 6 classifications and 23 subgroups were created. Overall pooled estimates with inverse‐variance weights obtained from a random‐effects model were estimated using the metaprop command in Stata. Results: Out of 19 320 studies, 263 were eligible for the narrative synthesis and 151 for meta‐analysis (total n  = 692 056, mean age: 68.5 years). Using different classifications and cut‐off points, the prevalence of sarcopenia varied between 10% and 27% in the studies included for meta‐analysis. The highest and lowest prevalence were observed in Oceania and Europe using the European Working Group on Sarcopenia in Older People (EWGSOP) and EWGSOP2, respectively. The prevalence ranged from 8% to 36% in individuals <60 years and from 10% to 27% in ≥60 years. Men had a higher prevalence of sarcopenia using the EWGSOP2 (11% vs. 2%) while it was higher in women using the International Working Group on Sarcopenia (17% vs. 12%). Finally, the prevalence of severe sarcopenia ranged from 2% to 9%. Conclusions: The prevalence of sarcopenia and severe sarcopenia varied considerably according to the classification and cut‐off point used. Considering the lack of a single diagnostic for sarcopenia, future studies should adhere to current guidelines, which would facilitate the comparison of results between studies and populations across the globe.